3D printing of cereal-based food structures containing probiotics. (October 2018) - Zhang, Lu; Lou, Yimin; Schutyser, Maarten A.I.
Graphical abstract: Highlights: It is feasible to produce cereal-based food structures containing probiotics using 3D printing. Printability of dough correlated to its rheological properties and microstructure. Increased surface-to-volume ratio of the structure accelerated its baking process. Viability of probiotics reached 10 6 CFU/g in the baked "honeycomb" structure. Abstract: The demand for foods with specific functionality and nutrition is increasing. This study investigated the feasibility of 3D-printing to manufacture cereal-based food structures containing probiotics. Dough formulations with different water content, wheat flour type and amount of calcium caseinate were evaluated in terms of printability during fused deposition modelling. The composition of dough influenced its rheological properties and microstructure which were correlated to its printability. Dough containing probiotics was printed into two types of structure with distinct surface-to-volume ratio, i.e., 9.20 cm 2 /cm 3 for the "honeycomb" design and 7.25 cm 2 /cm 3 for the "concentric" one. The printed structures were baked at 145, 175 and 205 °C, respectively. The survival of probiotics was not significantly different in these two structures after baking for the same time. However, increasing the surface-to-volume ratio of the structure accelerated its baking process. Thus, the viable counts of probiotics in the "honeycomb" structure exceeded 10 6 CFU/g when the end point of baking (at 145 °C) was set as the time required to reach a 6% moisture content reduction, which was 2 log higher than that in the "concentric" structure. The results reported in this study may benefit the development of innovative food products containing functional ingredients.